2019
DOI: 10.1093/mnras/stz920
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of magnetic reconnection powered blazar flares from synchrotron self-Compton emission

Abstract: Order of magnitude variability has been observed in the blazar sub-class of Active Galactic Nuclei on minute timescales. These high-energy flares are often difficult to explain with shock acceleration models due to the small size of the inferred emitting region, with recent particle-in-cell (PIC) simulations showing that magnetic reconnection is a promising alternative mechanism. Here, we present a macroscopic emission model physically motivated by PIC simulations, where the energy for particle acceleration or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…When adopting single-zone emission models under the assumption of equipartition, as is expected for reconnection driven blazar flares, BL Lac-like models are found to have Compton ratios of A C 0.1. More recently, the BL Lac plasmoid-emission models of PGS16, C19, and Morris et al (2019), showed that the average A C is ∼ 0.2, which falls near the lower bound of what is typically observed.…”
Section: Application To Bl Lac Sourcesmentioning
confidence: 74%
“…When adopting single-zone emission models under the assumption of equipartition, as is expected for reconnection driven blazar flares, BL Lac-like models are found to have Compton ratios of A C 0.1. More recently, the BL Lac plasmoid-emission models of PGS16, C19, and Morris et al (2019), showed that the average A C is ∼ 0.2, which falls near the lower bound of what is typically observed.…”
Section: Application To Bl Lac Sourcesmentioning
confidence: 74%
“…This region typically occupies only a few to ten percent of the merging plasmoids. Following the calculation in Morris et al (2019) for instance, the synchrotron photon energy density during plasmoid mergers will be higher than their estimates by at least one order, due to the highly inhomogeneous synchrotron emission. Since the SSC luminosity is proportional to the synchrotron photon energy density, this means that the Compton dominance is comparable to or larger than 1.…”
Section: Summary and Discussionmentioning
confidence: 90%
“…It is important to note that previous studies have found the Compton dominance, which is the ratio between the luminosity of the Compton scattering component over the synchrotron component, is typically less than 0.1 (Morris et al 2019;Christie et al 2019, however, see Christie et al 2020, which suggests that local Doppler boosting can enhance the Compton dominance). We note that these previous works generally assumed that the synchrotron photons are distributed over the entire plasmoid.…”
Section: Summary and Discussionmentioning
confidence: 91%
“…Further, the lepto-hadronic modeling was also used to modeled the SED of BL Lac where the high magnetic field and high proton power is required. A fast flare in BL Lac was also observed in very high energy (VHE) γ-ray by MAGIC and VERITAS in 2015 and 2016 and modeled by IC (MAGIC Collaboration et al 2020) and SSC mechanism (Morris et al 2019). For the comparison purpose, we have modeled the broadband SED of two instances as marked in Figure 7 by vertical pink dashed line.…”
Section: Broadband Sed Modelingmentioning
confidence: 95%